Analisis Hubungan Antara Kecelakaan Kerja Dengan Faktor-Faktor Yang Mempengaruhi Keselamatan Kerja Pada Perawat Di RS Robert Wolter Mongisidi Manado - Goretti Br Sembiring; Diana V.D. Doda; Fima L.F.G. Langi (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Occupational accidents among nurses are a serious concern, given the high exposure to biological, physical, and ergonomic hazards in hospital environments. Nurses face significant risks of needlestick injuries, musculoskeletal disorders, and work-related illnesses. Objective: This study aimed to analyze the prevalence and factors associated with occupational injuries and health problems among nurses at Robert Wolter Mongisidi Hospital, Manado. Methods: A cross-sectional study was conducted among 102 nurses using a census technique. Data were collected via an online questionnaire (Google Form). Statistical analyses included Chi-square tests, Mann-Whitney tests, and binary logistic regression. Results: The prevalence of occupational injuries was 16% (16/102) and occupational health problems was 19% (19/102). Among those injured, 44% did not report the incident. In multivariate analysis, work unit was the strongest predictor: nurses in outpatient units had odds ratio (OR) 12.37 (95% CI: 1.79–85.66; p = 0.011) and those in intensive/surgical units OR 5.81 (95% CI: 1.16–29.01; p = 0.032) for injuries compared to non-intensive inpatient units. Barriers to PPE use were significantly associated with occupational health problems (OR 3.84; 95% CI: 1.20–12.31; p = 0.024). Shorter work tenure increased the risk of occupational health problems (OR 0.83 per year; p = 0.041). Conclusion: High-risk work units, barriers to PPE use, and shorter work tenure are the main determinants of occupational injuries and health problems among nurses. Strengthening risk-based occupational health and safety programs, optimizing PPE availability and usage, and implementing K3 orientation programs for new nurses are recommended.